(untitled) (Journal of Multidisciplinary Sciences and Innovations, 2025)
This article analyzes the representation of orphans in Pearl S. Buck’s literary works, focusing on how these characters reflect the author’s social, cultural, and humanitarian concerns. Drawing on key texts such as “New Year,” “The Good Earth,” and “The Living Reed,” the article examines how Buck uses orphan figures to critique traditional family structures, gender inequality, and social neglect in both Chinese and Western contexts. The study highlights how orphans represent vulnerability, cultural change, and the potential for moral growth and redemption. By placing orphans at the center of emotional and moral conflict, Buck offers a compelling vision of compassion, resilience, and cross-cultural understanding.